Entrepreneurial marketing and social value creation in Turkish art industry An ambidextrous perspective - Ozdemir, Ozge Gokbulut (Emerald Group Publishing Ltd, 2013)
Purpose - The study seeks to extend the comprehension in entrepreneurial marketing (EM) and social value creation through searching the entrepreneurship process in the socially valued art industry. Design/methodology/approach - The study is based on a qualitative method: multiple case study. In total, six art-related innovative enterprises are chosen in different categories (art school, museum, art fair, art gallery, art media) in the art industry. Common properties of the cases are; creating social value in different scopes; and being pioneer and changing the rules in their fields as the entrepreneurial marketers. Findings - The result of the case study is based on the comprehensive model of entrepreneurship process and the findings are introduced in sub titles: antecedents of the entrepreneurship process; antecedents of non-profit and for-profit enterprises; ambidextrous entrepreneurship process; and ambidextrous dimensions of social value creation. Research limitations/implications - The study provides a new insight on social value creation and EM literature. Social implications - The art industry is closely related with social value creation and the study is valuable for filling the gaps between art and the entrepreneurship in this context. Originality/value - The study is valuable since it focuses on opportunity-related phases of entrepreneurship and introduces a holistic and process-based model in the context of cognitive and institutional environmental factors. The Ambidextrous Model of Entrepreneurship and Social Value Creation is valuable in order to inspire future researches, especially in EM.
Keywords: Entrepreneurialism; Marketing; Entrepreneurial marketing; Entrepreneurship process; Social entrepreneurship; Social value creation; Art industry